PENGARUH PERENDAMAN BENIH KAKAO DALAM AIR KELAPA DAN PEMBERIAN PUPUK NPKMg (15-15-6-4) TERHADAP PERTUMBUHAN BIBIT KAKAO ( Theobroma cacao L. ) - Puji Setiawan Puji Setiawan; Balonggu Siagian; Jonatan Ginting, Jonatan Ginting, (Jurnal Agroekoteknologi, 2013)
Coconut water is good in increasing the plant’s growth because it containsfitohormon and several growth vitamins. The right dosage of NPKMg fertilizationcan maximize the growth of cacao seedling. This research was conducted in desaTanjung Selamat kecamatan Medan Sunggal, start on January 2012 and end onMay 2012. The design used was a factorial randomized block design with twotreatment factors. The first factor is the duration of soaking in coconut water in 4stages, which are K0 (0 hour), K1 (6 hours), K2 (12 hours), dan K3 (18 hours).The second factor are the application of NPKMg fertilizer (15:15:6:4) in 4 stages:which are: P0 (0 g), P1 (7 g), P2 (14 g), P3 (21 g). The soaking of cocoa seeds incoconut water has significant effect on plant height and number of leaves.Interaction between soaking of cocoa seeds in coconut water and NPKMgfertilizer application has no significant effect on all parameters.Key words : coconut water, NPKMg fertilizer, cocoa, growth and production